Analisis Pengetahuan dan Sikap Remaja Tentang HIV/AIDS Sebagai Upaya Pencegahan Dini Terhadap Resiko Kehamilan Tidak Diinginkan di Era Digital - Yuhemy; Rini Mayasari (STIKes Budi Mulia Sriwijaya, 2025)
HIV/AIDS remains a significant global health problem. Data from WHO (2024) show that approximately 40.8 million people are living with HIV worldwide, with an increasing number of cases in Asia and Indonesia. Adolescents are considered a high-risk group due to varying levels of knowledge and attitudes toward HIV/AIDS, especially in the current digital era. This study employed a cross-sectional design to determine the relationship between the level of knowledge about HIV/AIDS and adolescents’ attitudes toward the disease. The population consisted of adolescents aged 15–18 years at SMA X Palembang, totaling 85 respondents selected using simple random sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability, then analyzed univariately and bivariately using the Spearman Rank test. Most respondents had a good level of knowledge (76.5%) and a positive attitude toward HIV/AIDS (65.9%). The Spearman Rank test showed a significance value of p = 0.000 < 0.05 and a correlation coefficient of r = 0.767 > 0.2383, indicating a significant relationship between the level of knowledge and adolescents’ attitudes toward HIV/AIDS. This study proves that the higher the adolescents’ knowledge level, the more positive their attitude toward HIV/AIDS. Good knowledge plays an essential role in reducing stigma and increasing empathy toward people living with HIV/AIDS. Continuous health education through schools, digital media, and outreach programs is needed to strengthen adolescents’ positive attitudes as part of early prevention efforts against HIV/AIDS and unwanted pregnancies in the digital era.